Regulation of tumor cell – Microenvironment interaction by the autotaxin-lysophosphatidic acid receptor axis - Tigyi, Gabor J. (Adv Biol Regul, 2018)
The lipid mediator lysophosphatidic acid (LPA) in biological fluids is primarily produced by cleavage of lysophospholipids by the lysophospholipase D enzyme Autotaxin (ATX). LPA has been identified and abundantly detected in the culture medium of various cancer cell types, tumor effusates, and ascites fluid of cancer patients. Our current understanding of the physiological role of LPA established its role in fundamental biological responses that include cell proliferation, metabolism, neuronal differentiation, angiogenesis, cell migration, hematopoiesis, inflammation, immunity, wound healing, regulation of cell excitability, and the promotion of cell survival by protecting against apoptotic death. These essential biological responses elicited by LPA are seemingly hijacked by cancer cells in many ways; transcriptional upregulation of ATX leading to increased LPA levels, enhanced expression of multiple LPA GPCR subtypes, and the downregulation of its metabolic breakdown. Recent studies have shown that overexpression of ATX and LPA GPCR can lead to malignant transformation, enhanced proliferation of cancer stem cells, increased invasion and metastasis, reprogramming of the tumor microenvironment and the metastatic niche, and development of resistance to chemo-, immuno-, and radiation-therapy of cancer. The fundamental role of LPA in cancer progression and the therapeutic inhibition of the ATX-LPA axis, although highly appealing, remains unexploited as drug development to these targets has not reached into the clinic yet. The purpose of this brief review is to highlight some unique signaling mechanisms engaged by the ATX-LPA axis and emphasize the therapeutic potential that lies in blocking the molecular targets of the LPA system.